2000
DOI: 10.1017/s0007114500001173
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional factors in stroke

Abstract: Observational studies support the role of modifying lifestyle-related risk factors such as diet, physical activity and alcohol use in stroke prevention. For example, increased Na intake is associated with hypertension, and reduction in salt consumption may significantly lower blood pressure and may reduce stroke mortality. Moderately elevated homocysteine levels may be associated with stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 96 publications
1
23
0
1
Order By: Relevance
“…Also, our dietary measures were general and may not capture dietary changes that are particular to stroke prevention. The association of dietary fat with stroke is uncertain, 36,39 although lower fat intake is recommended for the reduced risk of coronary heart disease, a risk factor for stroke. Other dietary factors that may be related to reduction in stroke risk include increased antioxidants and potassium through greater consumption of fruits and vegetables and reduced salt intake, which may lower high blood pressure, the major risk factor for stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, our dietary measures were general and may not capture dietary changes that are particular to stroke prevention. The association of dietary fat with stroke is uncertain, 36,39 although lower fat intake is recommended for the reduced risk of coronary heart disease, a risk factor for stroke. Other dietary factors that may be related to reduction in stroke risk include increased antioxidants and potassium through greater consumption of fruits and vegetables and reduced salt intake, which may lower high blood pressure, the major risk factor for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Other dietary factors that may be related to reduction in stroke risk include increased antioxidants and potassium through greater consumption of fruits and vegetables and reduced salt intake, which may lower high blood pressure, the major risk factor for stroke. 39 Results of recent studies, such as the Dietary Approaches to Stop Hypertension diet (for lowering high blood pressure) 40 and the Lyon Diet Heart Study 41 (demonstrating significant reductions in subsequent cardiovascular events after a myocardial infarction from the adoption of a Mediterranean diet), highlight the need for more well-designed studies examining the effects of lifestyle changes for secondary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The overall picture seems to be a good deal of epidemiological evidence linking nutrients and diet patterns to stroke risk, with no consistent distinction between ischaemic and haemorrhagic types 97 . As one might have predicted, these links have much in common with the nutritional associations to ischaemic and hypertensive cardiovascular disease generally.…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by Zoccali et al [26] demonstrated a linear association between Na consumption and daily blood pressure figures in middle-aged individuals [27, 28]. Yet, the evaluation of impact sodium intake has on the development of hypertension in the general population remains a subject of controversy.…”
Section: Resultsmentioning
confidence: 99%